2019
DOI: 10.1016/j.chempr.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystalline Tactoidal Microphases in Ferrofluids: Spatial Positioning and Orientation by Magnetic Field Gradients

Abstract: Macroscopic manipulation of self-assembly in lyotropic systems, such as chiral nematic liquid crystals formed by cellulose nanocrystals, is kinetically hindered by the similarity between isotropic and anisotropic phases in composition and physical properties. By creating a significant difference in volumetric magnetic susceptibility between discrete liquid crystalline tactoids and continuous isotropic phases (based on the exclusion effects of tactoids on superparamagnetic doping nanoparticles), we achieved pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…Due to the very sensitive conditions, experimental measurements of the elastic constants remain nontrivial and time consuming. Moreover, water-based biological CLC such as cellulose nanocrystals (CNC) and amyloid fibrils are weakly sensitive to electric and magnetic fields, and the measurement of the elastic constant for these systems is extremely elusive [43][44][45] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the very sensitive conditions, experimental measurements of the elastic constants remain nontrivial and time consuming. Moreover, water-based biological CLC such as cellulose nanocrystals (CNC) and amyloid fibrils are weakly sensitive to electric and magnetic fields, and the measurement of the elastic constant for these systems is extremely elusive [43][44][45] .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a range of fully cellulose-derived advanced and functional materials and (nano)composites can be prepared by selecting the correct raw materials and their combinations [ 2 , 3 , 4 , 5 , 6 ]. Furthermore, the inherent relative ease of modifiability makes cellulose applicable in a wide range of conditions and enables synergies with other materials, such as carbon nanotubes, graphene, other biomolecules, and metallic nanoparticles [ 7 , 8 , 9 , 10 , 11 , 12 ]. Potential applications for advanced cellulosic materials include: biomedicine, tissue engineering, photonics, smart materials, emulsions, foaming, and sensors [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 41 ] MacLachlan and coworkers demonstrated that gradient magnetic field in ferrofluids provided an effective means to control the position and orientation of liquid crystalline tactoids of CNCs, which may facilitate the formation of new mesophases. [ 42 ] Zhu and coworkers showed that the addition of a small amount of Fe 3 O 4 ‐coated CNCs into homogeneous CNC suspensions allowed tuning of the helical pitch using ultrasmall magnetic field. [ 43 ] To our knowledge, approaches to control over the self‐assembly to produce left‐handed chiral nematic CNC films with homeotropic concentric helix orientations in the planar textures displaying plane‐lateral chiroptical properties remain unexplored.…”
Section: Introductionmentioning
confidence: 99%